Survey of ‘Low-Z’ Particles from the Interplanetary Dust Collection in Search of IDPs - Wiesman, Harison (Washington University Open Scholarship, 2014)
Micrometeorites are one of the most common types of extraterrestrial material that fall to the Earth, beside meteorites and interplanetary dust particles (IDPs). All of these materials are known to contain presolar grains that, when studied in the laboratory, provide information about the origin of the solar system and help to constrain models of nucleosynthesis in stars. Recent studies of micrometeorites revealed the presence of a group of particles with very high C contents. These ultra-carbonaceous Antarctic micrometeorites (UCAMMs) are fine-grained, fluffy particles dominated by highly disordered carbonaceous matter. The presence of H and N isotopic anomalies, abundant presolar grains, and other minerals suggest similarities to IDPs. The presence of these ultra-carbonaceous particles led us to question if similar particles may be present in the NASA interplanetary dust collection. These particles undergo preliminary SEM-EDX analysis after being collected in the upper-stratosphere to separate IDPs from terrestrial contaminants. Some of the particles classified as terrestrial contaminants have spectra suggesting that they are dominated by low atomic number (low-Z) elements that are typically not detectable by EDX analysis. Although classified as terrestrial contaminants, some of these particles may in fact be extraterrestrial ‘low-Z’ IDPs with high C contents, similar to UCAMMs. In this study, we examined a number of low-Z particles to investigate this possibility. Using more sensitive EDX equipment, Raman analysis, and NanoSIMS isotopic imaging we showed that it is unlikely any of these low-Z particles contain presolar material, making it unclear whether or not these particles have an extraterrestrial origin.